Handy washy / Syahrul Amirul Yahaya ...[et al.] - Yahaya, Syahrul Amirul; Md Azali, Muhammad Azri; Wakhi Anuar, Iman Muslim; Tukeran, Nurul Farah Najihah
Handy Washy is an innovation prototype that was inspired by the typical washing machine that already existed today. Nowadays, washing the clothes and the other things that we are wear are significantly need to done every day. But sometimes, people will face several problems to done the washing process in their entire days. So, this small matter will make people find it hard to wash their clothes when they want, even though the washing clothes process is quite simple and easy to done. Here, we will minimize the scope of our discussion about the problems faced by people. In other words, we will target student community as our main customer to use our product. Most of the students, especially who are staying at the colleges will find it trouble for them to wash their clothes frequently. This is because there are no washing machine was placed at their colleges. The purpose of this prototype is to show the function of mechanical energy in generating works. This prototype will operate using foot-pedal that acts as mechanical part, also as the most important things that ensure this prototype is working. Besides that, this prototype had been designed with a few improvements that make it difference with the same classified products that available in marketplace. We had equipped this kind prototype with tyres at the bottom and added on a heater to make the washing process becomes more complete. In order to designing our product, we had made some online survey that were gave to among of students that were stayed at the college in UITM Pasir Gudang. Most of the respondent were unanimously agreed with one of the design that showed in the survey. Through the existing of our prototype, we hope it will made a huge impacts to the students that always facing problems during the washing process of their clothes at the college. By using this product, we hopefully they can feels ease when they want to wash the clothes, and also to make them not expected that washing clothes process is not something that can burden them